NEW BOBATH CONCEPT APPROACH IN ADOLESCENT WITH TRAUMATIC INTRACEREBRAL HEMORRHAGE (TICH): A CASE STUDY - Mufidati, Husna; Rahayu, Umi Budi; Kurniawan, Adhy (Universitas Muhammadiyah Surakarta, 2021)
Introduction : This case report shows the application of the exercise therapy method with the New Bobath Concept Approach in cases of Traumatic Intracerebral Hemorrhage (TICH) and reports the results of the exercise. Case presentation: Mr. AR, a 16-year-old student with a clinical diagnosis of Traumatic Intracerebral Hemorrhage (TICH) received an exercise therapy program with a New Bobath Concept Approach consisting of abdominal exercise, facilitate foreward & backward pelvic, bridging exercise, sensibility exercise, sitting and sitting balance exercise, mobilization and facilitation of the scapula and arm, core stability exercise, standing exercise, facilitation of walking patterns and walking exercise. Management and outcome: Exercise was carried out for 12 weeks with a frequency of twice a week and a duration of 60 minutes per training session. Discussion: After giving exercise therapy with the New Bobath Concept Approach for 12 weeks, the results showed an increase MMT value in muscles shoulder, elbow, wrist, fingers, hip and knee from 0 to 2 and 3. Meanwhile for the Barthel index from a value of 2 (total dependence) to 10 (moderate dependence). Conclusion: Mr. AR is able to sit, stand independently and walk 100 meters with assistance.